1973
DOI: 10.1515/znb-1973-1-216
|View full text |Cite
|
Sign up to set email alerts
|

Über Substituenten-Einflüsse auf die Bindungsverhältnisse der Metall-Komplexe des Cyclobutadiens / The Influence of Substituents on Bonding Properties in Metal Complexes of Cyclobutadiene

Abstract: The syntheses of some p- substituted phenylcyclobutadieneirontricarbonyls are reported. Carbonyl stretching frequencies, 13C-H- and H-Η-coupling constants are discussed with respect to bonding properties. There is apparently no conjugative interaction between the π-electron systems of cyclobutadiene and the phenyl ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1973
1973
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The organic chemistry of the cyclopentadienyl ligand in (cyclopentadienyl)(tetraphenylcyclobutadiene)cobalt (63) was investigated rather extensively by Rausch the following: acetomercuration in the presence of perchloric acid as catalyst (to afford 160 and 161); Vilsmeier formylation with /V-methylformanilide and phosphorus oxychloride (to afford 162); Mannich-typeaminomethylationwithbis(dimethylamino)methane and phosphoric acid (to afford 163); and Friedel-Crafts acetylation using acetic anhydride and boron trifluoride (to afford 164, in trace amounts only) (see Scheme XXVIII). Interestingly, the Friedel-Crafts acylation of 63 with benzoyl chloride and aluminum chloride gave a product (~1% yield) in which substitution appeared to have occurred on a phenyl rather than the cyclopentadienyl ring.…”
Section: Chemistry Of Cyclobutadienemetal Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…The organic chemistry of the cyclopentadienyl ligand in (cyclopentadienyl)(tetraphenylcyclobutadiene)cobalt (63) was investigated rather extensively by Rausch the following: acetomercuration in the presence of perchloric acid as catalyst (to afford 160 and 161); Vilsmeier formylation with /V-methylformanilide and phosphorus oxychloride (to afford 162); Mannich-typeaminomethylationwithbis(dimethylamino)methane and phosphoric acid (to afford 163); and Friedel-Crafts acetylation using acetic anhydride and boron trifluoride (to afford 164, in trace amounts only) (see Scheme XXVIII). Interestingly, the Friedel-Crafts acylation of 63 with benzoyl chloride and aluminum chloride gave a product (~1% yield) in which substitution appeared to have occurred on a phenyl rather than the cyclopentadienyl ring.…”
Section: Chemistry Of Cyclobutadienemetal Complexesmentioning
confidence: 99%
“…In most instances the mass spectra of cyclobutadienemetal complexes were obtained in order to establish the molecular weight from the molecular ions (Ml), although in few isolated cases brief discussions pertaining to some of the other spectral features have also been reported. More detailed studies of fragmentations taking place under electron-impact conditions were reported for complexes such as Ph4C4Fe(CO)3 (2),309 Ph4C4CoQ [Q = cyclopentadienyl (63) and indenyl],309 C8H6Fe(CO)2L [L = CO, Ph3P, Ph3As, and Ph3Sb],191 of a coordinated cyclobutadiene [R4C4M+, where M indicates either metal and/or metal bonded to some other ligand(s)] occurs by a two-step sequence involving successive losses of two acetylene (R2C2) fragments. This characteristic fragmentation pattern, pathway A in Figure 4, has been found in virtually all of the available mass spectra of cyclobutadienemetal complexes.…”
Section: E Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…3-( p -Tolyl)-3-cyclobutene-1,2-dione (14b). Method C: yellow crystals; mp 158−160 °C dec (acetone), (lit . mp 166 °C); yield 1.00 g (58%); IR 1765 (vs, br), 1600 (m) (CO, CC) cm -1 ; 1 H NMR (CDCl 3 ) δ 2.43 (s, 3H), 7.34 (d, 2H, J = 8.1 Hz), 7.86 (d, 2H, J = 8.1 Hz), 9.45 (s, 1H); 13 C NMR (CDCl 3 ) δ 22.07, 124.79, 129.50, 130.35, 146.17, 177.14, 195.44, 195.75, 198.06; MS m/z (relative intensity) 172 (M + , 18), 116 (100), 89 (11).…”
Section: Methodsmentioning
confidence: 99%
“…3-(4-Chlorophenyl)-3-cyclobutene-1,2-dione (14f). Method C: yellow crystals; mp 179−181 °C dec (acetone), (lit …”
Section: Methodsmentioning
confidence: 99%